2020
DOI: 10.1155/2020/8427574
|View full text |Cite
|
Sign up to set email alerts
|

An Amalgamated Approach to Bilevel Feature Selection Techniques Utilizing Soft Computing Methods for Classifying Colon Cancer

Abstract: One of the deadliest diseases which affects the large intestine is colon cancer. Older adults are typically affected by colon cancer though it can happen at any age. It generally starts as small benign growth of cells that forms on the inside of the colon, and later, it develops into cancer. Due to the propagation of somatic alterations that affects the gene expression, colon cancer is caused. A standardized format for assessing the expression levels of thousands of genes is provided by the DNA microarray tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Indeed, a computer-aided diagnosis system for skin cancer based on soft computing techniques, including CNNs and satin Bowerbird optimization (SBO), was introduced in the work of Xu et al 65 The system demonstrated high accuracy, sensitivity, and specificity compared with other methods in the literature. A combined approach to bilevel feature selection techniques using soft computing methods for classifying colon cancer was proposed in the work of Prabhakar et al 66 The method combined the multivariate minimum redundancy–maximum relevance (MRMR) technique with optimization techniques such as invasive weed optimization (IWO) and teaching learning-based optimization (TLBO). The approach achieved a classification accuracy of 99.16% when using quadratic discriminant analysis (QDA).…”
Section: Artificial Intelligence Application To Cancer Researchmentioning
confidence: 99%
“…Indeed, a computer-aided diagnosis system for skin cancer based on soft computing techniques, including CNNs and satin Bowerbird optimization (SBO), was introduced in the work of Xu et al 65 The system demonstrated high accuracy, sensitivity, and specificity compared with other methods in the literature. A combined approach to bilevel feature selection techniques using soft computing methods for classifying colon cancer was proposed in the work of Prabhakar et al 66 The method combined the multivariate minimum redundancy–maximum relevance (MRMR) technique with optimization techniques such as invasive weed optimization (IWO) and teaching learning-based optimization (TLBO). The approach achieved a classification accuracy of 99.16% when using quadratic discriminant analysis (QDA).…”
Section: Artificial Intelligence Application To Cancer Researchmentioning
confidence: 99%
“…Understanding the relation between the gene and its products is a contribution to the genetic approach to cancer diagnosis, so that the identification of biomarker genes for targeting drug therapies can be understood well [ 4 ]. With this approach, the effects of genes on some cell signaling pathways can be well understood [ 5 ]. The information about active levels of a gene is provided by the gene expression.…”
Section: Introductionmentioning
confidence: 99%